Legal Issues Related to Listening to Digital Evidence in Civil Cases - Nueangnong, Visitsak; Itthimechai, Thitirat; Pramarn, Songporn; Nilyan, Duangthip (วารสารสหวิทยาการสังคมศาสตร์และการสื่อสาร, 2022)
The world has evolved into a digital era of communication, transactions, and almost all of life. Most human beings need to use relevant electronic devices to make transactions and do those things, including data access, collection, and transmission, more accessible and faster. As a result, it is another channel for criminals to use to commit crimes. Civil digital evidence is unique in that it can easily alter, and that amendment can damage information. It allows digital evidence to be credible and listenable in judicial and judicial processes. Therefore, dealing with digital evidence requires a standardized, universally accepted, and reliable method. In particular, the various technical guidelines for dealing with digital evidence. The researcher has presented a guideline to amend and add to the Thai jurisprudence method and clearly define electronic data to clarify what kind of evidence. It is classified as prescribing rules and procedures for an inheritance to have specific characteristics to suit the complex nature of electronic evidence that will directly affect the use of electronic contracts as evidence, including the determination of the authenticity and completeness of electronic data. It is because the state of electronic data can be easily changed and modified by having a specific body established to ensure electronic data. It will be used as evidence to provide credibility, and information has not been modified or altered, including learning, and developing processes related to digital evidence in civil cases. It can determine the work direction that creates credibility and can be used in the judicial process. It is for Thailand to have a law relating to the adequate hearing of witnesses. As a result, the law on hearing digital evidence in civil cases will be more accepted and credible.